2002
DOI: 10.1149/1.1466858
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Interactions among Localized Corrosion Sites

Abstract: Interactions among local pit sites were investigated using a 5 ϫ 5 array of 25 electrodes consisting of closely spaced, flushmounted 316 stainless steel wires. Three types of interactions occurred when actively corroding pits existed while the remaining electrodes were initially passive in 0.05 M NaCl solution. Suppression of pitting on nearby electrodes occurred due to ohmic potential drop near pre-existing pits. Enhancement of pitting at initially passive electrodes was observed and attributed to both tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 28 publications
4
77
0
Order By: Relevance
“…Therefore, corrosion spreads affecting the entire surface in a sequential way with increasing current density in the galvanodynamic curve. It seems that the corrosion products catalyze the subsequent corrosion processes, this behaviour being according to the literature (33)(34)(35)(36)(37). Every time that the corrosion product forms a new circle and corrosion begins to affect a greater area of the electrode, a potential peak appears in the galvanodynamic curves (peaks are marked with numbers from 3 to 6 for both samples in Figure 3).…”
Section: Ecs Transactions 41 (24) 45-54 (2012)mentioning
confidence: 53%
“…Therefore, corrosion spreads affecting the entire surface in a sequential way with increasing current density in the galvanodynamic curve. It seems that the corrosion products catalyze the subsequent corrosion processes, this behaviour being according to the literature (33)(34)(35)(36)(37). Every time that the corrosion product forms a new circle and corrosion begins to affect a greater area of the electrode, a potential peak appears in the galvanodynamic curves (peaks are marked with numbers from 3 to 6 for both samples in Figure 3).…”
Section: Ecs Transactions 41 (24) 45-54 (2012)mentioning
confidence: 53%
“…They occur at potentials lower than the E pit , being the critical potential for pit stabilization. Spatial and temporal interactions among metastable pits leading to clustering and hence high corrosion rates of stainless steel were investigated thoroughly over last decade within the context of nonlinear dynamics and pattern formation (Lunt et al, 2002;Mikhailov et al, 2009;Organ et al, 2005;Punckt et al, 2004). The potential region where these current transients appear is distinctly different from the potential region within which the large-amplitude complex passive-active current oscillations, discussed in this article, arise.…”
Section: Discussionmentioning
confidence: 99%
“…Steadystate processes leading to passive and active states of Fe in a halide-free sulfuric acid solution are perturbed through a series of physico-electrochemical reactions including autocatalytic steps. In fact, pit nucleation, propagation and growth are autocatalytic processes Lunt et al, 2002;Macdonald, 1992). Pit repassivation or stable growth can be realized by investigating the system oscillatory states and oscillation waveform.…”
Section: Alternate Diagnostic Criteria To Characterize Pitting Corrosmentioning
confidence: 99%
“…When a pit begins to form (and current flows), its local environment is altered, i.e., when the metal Reproduced from [72] by permission of The Electrochemical Society dissolves and its cation enters the solution, the interaction with water molecules (hydrolysis) enhances the local acidity, and the electroneutrality condition causes the local increase in anion (chloride) ion concentration. Already in 1991, Harb and Alkire [62] have shown that such concentration gradients develop in the solution for a distance of up to three pit diameters.…”
Section: The Pitting Corrosion Of Steel As a Cooperative Processmentioning
confidence: 99%